2022
DOI: 10.3389/fpls.2022.851077
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Elicitor-Induced Camptothecin Biosynthesis in Camptotheca acuminata Plantlets Through a Combined Omics Approach

Abstract: Treatments with abiotic elicitors can efficiently induce the accumulation of specialized metabolites in plants. We used a combined omics approach to analyze the elicitation effects of MeJa, AgNO3, and PEG on camptothecin (CPT) biosynthesis in Camptotheca acuminata plantlets. Untargeted analyses revealed that treatments with MeJa, AgNO3, and PEG significantly inhibited the photosynthetic pathway and promoted carbon metabolism and secondary metabolic pathways. The CPT levels increased by 78.6, 73.3, and 50.0% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…The whole genomes of the both CPT‐producing plants have been sequenced and assembled (Kang et al, 2021; Rai et al, 2021; Zhao et al, 2017), which has boosted the discovery and characterization of genes involved in CPT biosynthesis. In addition, considerable effort has been directed at elucidating the CPT biosynthetic pathway from a multiomics perspective (Pu et al, 2020; Pu et al, 2022). For example, Pu et al identified a series of CPT analogues and found 12 candidate CYP450s possibly involved in the biosynthesis of CPT and its derivatives based on Illumina sequencing and metabolite analysis (Pu et al, 2020, Pu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The whole genomes of the both CPT‐producing plants have been sequenced and assembled (Kang et al, 2021; Rai et al, 2021; Zhao et al, 2017), which has boosted the discovery and characterization of genes involved in CPT biosynthesis. In addition, considerable effort has been directed at elucidating the CPT biosynthetic pathway from a multiomics perspective (Pu et al, 2020; Pu et al, 2022). For example, Pu et al identified a series of CPT analogues and found 12 candidate CYP450s possibly involved in the biosynthesis of CPT and its derivatives based on Illumina sequencing and metabolite analysis (Pu et al, 2020, Pu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, considerable effort has been directed at elucidating the CPT biosynthetic pathway from a multiomics perspective (Pu et al, 2020; Pu et al, 2022). For example, Pu et al identified a series of CPT analogues and found 12 candidate CYP450s possibly involved in the biosynthesis of CPT and its derivatives based on Illumina sequencing and metabolite analysis (Pu et al, 2020, Pu et al, 2022). It is thus clear that multiomics technologies play an important role in revealing the biosynthesis and regulation of CPT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It indicates that TFs in MYB, WRKY, AP2/ERF and bHLH are likely to regulate spiroindole alkaloid production in U. rhynchophylla . In addition, the members of the CYP71 and CYP81 families are usually involved in indole alkaloid, flavonoid, and terpenoid metabolism [ 28 ]. The unigenes of the CYP71 and CYP81 families shown in Figure 9 are also possible candidates for spiroindole alkaloid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%